Keefektifan Model Pembelajaran Problem Based Learning untuk Meningkatkan Keaktifan dan Hasil Belajar Siswa - Maya Soleha; Iis Ristiani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study aims to prove the effectiveness of the problem-based learning model on negotiation text writing skills in Grade XI students of Cianjur Health Vocational School. This research is an experiment-based research involving one class. The population in this study is 361 students in grade XI of SMK Kesehatan Cianjur spread across ten classes. The selected research sample is grade XI students with a total of 35 students. Sample withdrawal was carried out using a simple random sampling technique. The assessment instruments used in the study are instruments related to the implementation of learning to write negotiation texts using a problem-based learning model and a performance test for writing negotiation texts. The test is used in the initial test (pretest) and final test (postest). The data obtained were then analyzed using descriptive statistical methods and inferential statistics. The results of descriptive statistics show that the problem-based learning model is effective on the ability to write negotiation texts in grade XI students of SMK Kesehatan Cianjur. This is evidenced by the test scores taught using a problem-based learning model in the medium category with an average score of 78.9. The results of inferential statistics for the calculation of the significance test of the t-test t-value of the t-count value > ttable, which are 4.268 > 1.690. This shows that the hypothesis proposed is accepted, which means that the problem-based learning model is effective for the ability to write negotiation texts which is carried out in class XI of SMK Kesehatan Cianjur. Based on the presentation of the results of the data analysis and discussion, it can be concluded about the effectiveness of the Problem Based Learning model on negotiation text writing skills in grade XI students of SMK Kesehatan Cianjur. Based on these conclusions, several suggestions can be put forward in relation to the results of this study. One of them is for Indonesia Language and Literature teachers, especially Class XI of SMK Kesehatan Cianjur, trying to enrich the learning model of writing negotiation texts and always provide training to students in writing texts and for students it is hoped that they can get used to writing negotiation texts to make it easier and vary their work.